Use the Chain Rule to differentiate the following equation: y=e^(3-2x)

Chain Rule: dy/dx = dy/du x du/dxy=e3-2xSubstitute u for the power (3-2x) y = eu u = 3-2xdy/du = eu du/dx = -2dy/dx = -2eu = -2e3-2x

Answered by Jordan W. Maths tutor

3300 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do I integrate x/(x^2 + 3) ?


Differentiate x^3 + 6x + 1


When do you know to use integration by parts?


Demonstrate that (2^n)-1 is not a perfect square for any n>2, n ∈ N.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences